Social Media for the Hepato-Pancreato-Biliary community (#SoMe4HPB): connecting a specialized online group for scientific and clinical knowledge dissemination. Issue 9 (September 2021) - Sgarbura, Olivia; Mackenzie, Graham; Holmberg, Marcus; Wigmore, Stephen J.; Søreide, Kjetil
Abstract: Background: Social media has an increasingly important role in scientific communication, clinical discussions and knowledge distribution. While several surgical disciplines have taken to internet for increased connectivity, there is currently little knowledge about the social media activity in the field of hepatopancreatobiliary surgery. We aimed to evaluate the implementation and use of a specific HPB hashtag and Twitter handle. Methods: The hashtag and Twitter handle (#SoMe4HPB; @hpb_so) were initiated on February 2019. We evaluated the response during the initial 15 months by applying NodeXL to trace activity. Results: The Twitter handle had 1388 followers (by May 7, 2020) and had generated 855 tweets and retweets. A total of 1120 mentions of 182 accounts were recorded in original tweets by @hpb_so. The largest global reach was recorded in December 2019 (254.000 people). Pancreatic cancer was the subject of 15% of all posts, liver malignancies of 12% of all posts and minimally invasive surgery of 8%. Conclusion: The Social Media for the Hepato-Pancreato-Biliary community (#SoMe4HPB) and its associated Twitter handle @hpb_so had a well-built inception followed by a progressive development connecting individuals interested in HPB Surgery internationally. The involvement of more actors is required in order to fully attain its scientific dissemination role.